Effects of severe weather on shorebirds: Evidence of disrupted refueling and delayed departure on southbound migration - Sophia M. Fraser; Devin R. deZwaan; Hilary A. R. Mann; Julie Paquet; Diana J. Hamilton (Ecosphere)
Abstract Severe weather events are more frequently impacting wildlife, especially in climate‐sensitive ecosystems like coastal habitats. A particularly vulnerable stage for migratory species is juvenile movement between natal and non‐breeding habitats. Globally, coastal habitats represent critical stopover or staging sites during postbreeding migration for many shorebird species. At these sites, individuals must accumulate necessary energy stores (i.e., fats and proteins) to fuel what are often long‐distance, over‐water flights to reach their final destination. Inexperienced juvenile shorebirds in unfamiliar habitats may be particularly susceptible to extreme weather events that alter habitat structure and resource availability, with potential implications for refueling efficiency and migration success. However, few studies have addressed the effects of extreme weather at staging sites, limiting our understanding of the capacity of birds to respond to or recover from acute disturbances. We used a before–after framework to investigate how Hurricane Fiona affected the staging behavior of juvenile semipalmated plovers (Charadrius semipalmatus) in Atlantic Canada during southbound migration. We combined morphometric analyses, automated radiotelemetry tracking, and invertebrate sampling to assess storm effects on relative fuel load, bivalve prey availability, and length of stay in the region. Birds captured poststorm lost an estimated 78% of their relative fuel load compared to prestorm birds, coinciding with an estimated 70% decline in bivalve availability. Individuals who experienced the storm approximately doubled their length of stay. Given that juvenile shorebirds undertake southbound migration later in the season than adults, we predict juveniles will be impacted disproportionately by late‐season tropical storm patterns, with potentially substantial impacts on shorebird populations. We emphasize the need for a greater research focus on extreme weather during vulnerable life‐history stages, like migration, for a broader understanding of how species will respond to increasingly intense storm events.